Background of the Creation of Heri Dono’s Wayang Legenda as a Basis of Developing Local Resource-Based Creativity - Widiyastuti, Endang; Rohidi, Tjetjep Rohendi; Florentinus, Totok Sumaryanto (Universitas Negeri Semarang, 2018)
The education of art and culture contributes to the development goals of the Indonesian nation in the form of collective art (integrated art) of the whole art. Concretely, traditional art form in Indonesia can be found in wayang art. Globalization and the development of ICT in the show world now have a negative impact on the lack of interest of the younger generation to recognize the performance of wayang art, especially Solo cultural city. The research on the background of the creation of the Heri Dono puppet legend involves the aspect of the idea (source of ideas) that underlies the artist in the wayang puppets' way of being a new wayang. This research uses qualitative-descriptive approach. The object of research is the process of making and events Wayang Legend show. Sources of research data are informants, places, events, and documentation. Data obtained through observation techniques, interviews, and content analysis to examine existing document study, purposive sampling, and snowball sampling. The validity of the data is tested by triangulation of sources and methods. Data were analyzed using interactive analysis technique.The background of the Wayang Puppet creation Heri Dono stood on the consciousness of presenting himself, turning to tradition, and beginning in the 1980s. Experiencing puppet characters is related to understanding puppet show stories. Heri Dono reaffirms his belief that art is not separated from culture. Underlying his art making, he feels the need to develop the sensitivity to listen to the sounds and music, the sensitivity to motion and the sensitivity of telling. Heri Dono created two series of Legend Puppet: in 1988